Oligocene Palynological Zonation Scheme From East Java Sea - Eko Budi Lelono; Robert J Morley (Scientific Contributions Oil and Gas, 2011)
Systematic biostratigraphic analyses have been undertaken on the Oligocene clastic and carbonate Kujung Formation from the East Java Sea, North of Madura. The succession has been examined mainly using cutting samples in two wells, using a combination of foraminiferal, nannofossil and palynological analyses at regular spacing. Nannofossil analysis indicates that the Late Oligocene to basal Early Miocene succession is more or less complete, with zones NP24, NP25 and NN1 are all being well developed. In addition, the Early Oligocene is indentified by larger foraminifera indicating the Tc/ Td Letter Stage. Because the traditional palynological zonation of Morley (1978) does not work well in this area, the succession has been divided into broad assemblage zones, which appear to be controlled mainly by climate. These zones are OL-1, OL-2, OL-3, OL-4 and OL-5. Zone OL-1 is based essentially on the absence of seasonal climate and riparian elements, whilst zone OL-2 is characterized by the regular occurrence of seasonal climate elements, especially of Malvacipollis diversus. Zone OL-3 is indicated by common to abundant Dacrydium and Casuarina pollen, with a strong acme of dinoflagellate cysts dominated by Operculodinium spp. and Spiniferites spp., whereas zone OL-4 is marked by abundant Dacrydium and regular Casuarina pollen, but low representation of riparian elements. Finally, the youngest zone is OL-5 which is characterized by reduced Dacrydium and Casuarina pollen, and increased riparian elements. The above palynological zonation suggests climate change, which closely parallels the climate succession from West Java Sea (but with changes less pronounced). Therefore, this study provides a well dated Oligocene palynological zonation which can be applied across Java.